2019
DOI: 10.1111/bjd.18058
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic metabolic markers in cutaneous melanoma

Abstract: Summary Melanoma is the most aggressive skin tumour, being the leading cause of death from skin cancer. Its incidence has increased more rapidly than for any of the top 10 cancers. A low percentage of patients with metastasis (meaning it has spread to other parts of the body) survive over one year after diagnosis, due to the lack of efficient therapy. Not all melanomas are the same, they can vary in how aggressive they are (how quickly they develop and potentially spread) and in their appearance. The authors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Metabolic changes are observed in most cancer cells, including accelerated nutrient import and metabolic rewiring to enhanced aerobic glycolysis [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Alterations in lipid metabolism and the development of a lipogenic phenotype have also emerged as early biochemical hallmarks of cancer cells [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic changes are observed in most cancer cells, including accelerated nutrient import and metabolic rewiring to enhanced aerobic glycolysis [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Alterations in lipid metabolism and the development of a lipogenic phenotype have also emerged as early biochemical hallmarks of cancer cells [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in lipid metabolism and the development of a lipogenic phenotype have also emerged as early biochemical hallmarks of cancer cells [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In this regard, studies assessing the metabolic behavior of melanoma have demonstrated that such phenotypic plasticity confers adaptive advantages favoring proliferation and survival [ 4 , 19 , 20 ]. For instance, while the de novo biosynthesis of fatty acids (FA) is mild in normal adult tissues, the tumorigenesis-associated increase in lipid production enables cells to create a strategically structured new biomass [ 12 , 13 ], helping them better handle changing environmental conditions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%